Aromatic reduced amide bond peptidomimetics as selective inhibitors of neuronal nitric oxide synthase - Hah, JM; Martasek, P; Roman, LJ; Silverman, RB (AMER CHEMICAL SOC, 2003)
Nitric oxide synthase inhibitors could act as important therapies for disorders arising from overstimulation or overexpression of individual nitric oxide synthase (NOS) isoforms. But preservation of physiologically important nitric oxide functions require the use of isoform-selective inhibitors. Recently we reported reduced amide bond pseudodipeptide analogues as potent and selective neuronal nitric oxide synthase (nNOS) inhibitors (Hah, J.-M.; Roman, L. J.; Martasek, P.; Silverman, R. B. J. Med. Chem. 2001, 44, 2667-2670). To increase the lipophilicity a series of aromatic, reduced amide bond analogues (6-25) were designed and synthesized as potential selective nNOS inhibitors. The hypothesized large increase in isoform selectivity of nNOS over inducible NOS was not obtained in this series. However, the high potency with nNOS as well as high selectivity of nNOS over endothelial NOS was retained in some of these compounds (15, 17, 21), as well as good selectivity over inducible NOS. The most potent nNOS inhibitor among these compounds is N-(4S)-{4-amino-5-[2-(2-aminoethyl)phenylamino]-pentyl}-N'-nitroguanidine (17) (K-i = 50 nM), which also shows the highest selectivity over eNOS (greater than 2100-fold) and 70-fold selectivity over iNOS. Further modification of compound 17 should lead to even more potent and selective nNOS inhibitors.
Keywords: CONTAINING DIPEPTIDE AMIDES; ESCHERICHIA-COLI; ARGININE; RELEASE; POTENT